Student Motivation in Learning Sports and Health Physical Education At SLBN 033 Tembilahan* - rahmawati, gusti; indra putra, edi susrianto (FKIP Universitas Islam Indragiri, 2023)
The problem of this research is to find out how students are motivated in learning physical education, sports and health at SLBN 033 Tembialahan. This type of research is descriptive. When the research was carried out in September 2022. The place of research was SLBN 033 Tembilahan. The sample collection technique used in this study was